Optimalisasi Sistem Strategis: Evaluasi Implementasi Manajemen Talenta ASN pada Bagian Protokol dan Komunikasi Pimpinan Kota Batu - Akhmad Ivan Zulkarnaen; Octa Dwi Sofian; Cicilia Evie Dewantara; Iqbal Rulliansyah (STIA MALANG, 2026)
State Civil Servants (ASN) play an important role in supporting governance and public services. However, ASN career management still faces challenges in competency development, employee-organizational alignment, and merit system implementation. This study aims to analyze ASN talent management implementation in the Protocol and Leadership Communication Division of Batu City and identify its supporting and inhibiting factors. This research employed a qualitative descriptive approach using indepth interviews and document analysis. Data were analyzed through the interactive model of Miles, Huberman, and Saldaña (2014). The findings show that ASN talent management implementation includes talent identification and acquisition, competency development, employee retention, competency-based placement, and monitoring and evaluation. Supporting factors include leadership commitment, ASN BerAKHLAK values, and policy support, while the main challenges involve limited personnel information systems, uneven employee understanding, and the need for more specific competency development.